Metodologi Kritik Hadis Darquthni terhadap Riwayat Takfir dalam Shahih Al-Bukhari dan Relevansinya di Era Digital: The Methodology of Hadith Criticism by Darquthni on Takfir Narrations in Sahih al-Bukhari and Its Relevance in the Digital Era - Andi Lili Sukmawardani; Muhammad M. Ahdad; Ahmad Khaerussalam (AL ISNAD: Journal of Indonesian Hadith Studies, 2026)
This study analyzes Darquthni’s critique of the sanad (chain of transmission) of a hadis narrated by al-Bukhari concerning the act of declaring fellow Muslims as disbelievers (takfir), as well as its relevance in the context of takfir phenomena in the digital era. Employing a qualitative-analytical approach, this research examines Darquthni’s methodological framework in identifying ‘ilal (hidden defects) within the hadis’s chain of transmission. Although there is an indication of tadlīs (concealment of an intermediary narrator) on the part of Yahya ibn Abi Katsir, the findings reveal that the hadith can still be classified as sahih (authentic) based on a comparative analysis of al-Bukhari’s methodology and the assessments of other hadis scholars. The phenomenon of takfir on social media reflects an increasing tendency to declare others disbelievers without adequate methodological consideration, thereby underscoring the continued relevance of this hadis as an ethical and moral foundation in addressing such accusations in digital spaces. This study emphasizes that the authenticity of a hadis cannot be determined solely on the basis of a single sanad critique, but rather requires a comprehensive examination from multiple scholarly perspectives. It further highlights the importance of caution and a rigorous scholarly approach in responding to takfir phenomena in order to prevent division within contemporary Muslim communities.